Implementation of dynamic in the classroom and its incidence on children´s performance and motivation of fifth grade of basic education at Andres Sevilla Lauzo School in Guayaquil, during the school year May- December 2011 - Morán Macías, Luis Fernando (2011)
Through this research work it was determined the impact of the implementation of dynamic activities in classroom on the student´s performance and motivation in the fifth grade of the institution, which determine the listening, speaking, reading, and writing skills of these students, and that is specifically evident in the overall average achievement . According to this study it was determined the need to put into practice the application of dynamic activities as a learning tool on the level of development of the four skills in the educational process. Thus, by applying this pedagogical tools the dynamic activities in the classroom, the teaching / Learning process of listening, speaking, reading, and writing of English as a foreign language is improved and enhanced because the students are more motivated to learn when they are using the new tools like dynamic activities, which is very important in the development of the students¿ talents, aptitudes, and abilities, mainly in the four skills; furthermore when the students of Andres Sevilla School use these resources they can develop not only listening, reading and writing, but also all the other language learning skills, providing the students an integral education. In this study, the field, social and participatory research was applied and as a result, a proposal is made using an integrated tool with strategies that involve the students, the parents and the institution, by the means of teamwork and group support to get the effective application of the implementation of dynamic activities as a learning tool in the Classroom.